PERANCANGAN STANDAR OPERATIONAL PROSEDUR (SOP) PADA PROSES PRODUKSI FROZEN FOOD - Hapsari, Yaning Tri; Kurniawanti, Kurniawanti (Jurnal Terapan Abdimas, 2022)
Abstract. SME Minanisa is an SME in the field of frozen food industry. The production process at UKM Minanisa does not yet have written standards or procedures. This allows the occurrence of work accidents and the large variety of products produced in the production process. The purpose of this service is to design a written document that describes the sequence of work steps in production activities (SOP). This service is carried out by interview and observation to the business location. The result of this dedication is the design of SOP which is expected to improve the production process to run better.Abstrak. UKM Minanisa merupakan UKM yang bergerak di industri frozen food. Proses produksi pada UKM Minanisa belum memiliki standar atau prosedur yang tertulis. Hal ini memungkinkan terjadinya kecelakaan kerja dan banyaknya variansi produk yang dihasilkan di proses produksi. Tujuan dari pengabdian ini adalah merancang suatu dokumen tertulis yang menjelaskan urutan langkah-langkah kerja dalam kegiatan produksi (SOP). Pengabdian ini dilaksanakan dengan wawancara dan observasi di lokasi usaha. Hasil pengabdian ini adalah rancangan SOP yang diharapkan dapat memperbaiki proses produksi berjalan lebih baik.